The Global research of protein post-translational modifications in the cancer field: A bibliometric and visualized study - Ma, Ruixia; Zhang, Meigui; Xi, Jiahui; Li, Jing; Ma, Yinxia; Han, Binxiao; Che, Tuanjie; Ma, Zhihui; Tian, Jinhui; Bai, Zhongtian (Frontiers in Oncology, 2022)
Objectives: Protein post-translational modifications (PTMs) are closely associated with tumorigenesis, targeting PTMs of key proteins might be the focus of antitumor drug discovery. This study aimed to analyze the research progress on protein PTMs in tumorigenesis by performing qualitative and quantitative evaluations. Methods: The Web of Science Core Collection was selected as the database, and Science Citation Index Expanded was selected as the citation index. Visualization tools such as VOSviewer, CiteSpace, HistCite, and Online Analysis Platform of Bibliometrics were used to deeply explore the information of the retrieved research papers and analyze them in terms of research trends and main aspects of research. Results: The search yielded 3777 relevant articles. The results showed that the total number of PTMs related papers in cancer field has been increasing annually, with the largest number of papers published in the United States of America. The co-word cluster analysis showed that the research on PTMs and tumorigenesis was primarily focused on the following four areas, mechanism, histone, P53, key Technologies. Tumor metabolism, autophagy, and protein-protein interaction, histone ubiquitination have become new research topics. Conclusion: This study provides an important reference for the research direction and selection of topics of interest in the PTMs of cancer field.